2009
DOI: 10.1007/s12633-009-9007-1
|View full text |Cite
|
Sign up to set email alerts
|

Redox Initiated Cationic Polymerization: Reduction of Triarylsulfonium Salts by Silanes

Abstract: A novel redox initiator system for carrying out the cationic polymerization of epoxide, oxetane and vinyl ether monomers has been developed. The redox couple is based on a triarylsulfonium salt as the oxidant with an organosilane as the reducing agent. The reaction between these two agents is markedly catalyzed by platinum and palladium complexes. Cationic polymerizations using this redox initiator system were carried out in a conventional manner with neat monomer or under solution conditions. This paper also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Indeed, it is more difficult to reduce triarylsulfonium salts (E red = −28 kcal/mol) [188] than diaryliodonium salts (E red = −5 kcal/mol) [187]. One was successful using noble metal catalysts and vapor state silane for the polymerization of highly reactive activated epoxides and vinyl ethers [189]. These monomers show a better reactivity compared to classical epoxide ones (see below).…”
Section: Other Catalystsmentioning
confidence: 99%
“…Indeed, it is more difficult to reduce triarylsulfonium salts (E red = −28 kcal/mol) [188] than diaryliodonium salts (E red = −5 kcal/mol) [187]. One was successful using noble metal catalysts and vapor state silane for the polymerization of highly reactive activated epoxides and vinyl ethers [189]. These monomers show a better reactivity compared to classical epoxide ones (see below).…”
Section: Other Catalystsmentioning
confidence: 99%
“…In our previous work on redox initiated cationic polymerization, 4,5 we showed that silanes are powerful reducing agents for both diaryliodonium and triarylsulfonium salts whereas 9-borabicyclo[3.3.1]nonane (9-BBN) 7 was more selective, capable of reducing only the more easily reduced diaryliodonium salts. In view of the stability of N-aryl heteroaromatic onium salts, it appeared reasonable to attempt their reduction with the more powerful silane reducing agents.…”
Section: Study Of the Reduction Of N-aryl Heteroaromatic Onium Saltsmentioning
confidence: 99%
“…In a series of recent papers from this laboratory, [4][5][6][7] we have reported the development of a two new types of initiator systems for carrying out cationic polymerization reactions. These initiator systems are based on redox couples in which diaryliodonium and triarylsulfonium salts were used as the oxidants while a dialkylborane or various silanes bearing the SiAH group were used as the reducing agents.…”
mentioning
confidence: 99%
“…After an equilibration period of 20 s, a predetermined amount of the silane was added to the pan using a syringe while the monomer-catalyst-onium salt solution was rapidly stirred. All polymerizations were carried out at an initial temperature of [23][24][25] • C. During kinetic runs, the temperature of the sample was monitored at a rate of one measurement per second.…”
Section: Optical Pyrometrymentioning
confidence: 99%